2022
DOI: 10.1093/oso/9780192866028.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Politicians' Reading of Public Opinion and its Biases

Abstract: Politicians care a lot about public opinion, they put great effort into getting to know what the people want. They almost constantly assess public opinion through a large variety of sources. And although most of them define themselves as trustees, in their actual day-to-day decision-making almost all politicians behave as delegates in the sense that they hardly ever deliberately cross public opinion but act in line with it (or act not at all). Notwithstanding their great focus on public opinion, politicians’ p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Qualitative work on how politicians read public opinion indeed shows that public opinion signals often come to them unsolicited; e.g. via people who talk to them on the street (Walgrave et al, 2023b). Further, on salient issues voters' preferences are not only more visible but also more stable (Clausen, 1977(Clausen, , 1983Zaller, 1992;Howe and Krosnick, 2017).…”
Section: Salience As a Driver Of Perceptual Accuracymentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative work on how politicians read public opinion indeed shows that public opinion signals often come to them unsolicited; e.g. via people who talk to them on the street (Walgrave et al, 2023b). Further, on salient issues voters' preferences are not only more visible but also more stable (Clausen, 1977(Clausen, , 1983Zaller, 1992;Howe and Krosnick, 2017).…”
Section: Salience As a Driver Of Perceptual Accuracymentioning
confidence: 99%
“…For this second path to work, politicians must have an accurate understanding of the public's desires. Even though politicians go to great lengths to learn about the public's preferences (Soontjens & Walgrave, 2021: Walgrave et al, 2023b, their understanding of public opinion is frequently inaccurate (e.g., Holmberg, 2003;Broockman & Skovron, 2018;Pereira, 2021;Pilet et al, 2023;Walgrave et al 2023a). One recent study that draws on data from four countries finds that politicians do not have a significantly more accurate understanding of public opinion than ordinary citizens do (Walgrave et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, however, research on politicians' knowledge of constituents' preferences has not been encouraging; recent studies have found that politicians regularly misperceive public opinion by 20 percentage points or more (Broockman and Skovron 2018;Kalla and Porter 2019;Walgrave et al 2023). While elected representatives express a strong interest in public opinion (Walgrave et al 2022), politicians in many countries appear to systematically overestimate citizens' conservatism (Broockman andSkovron 2018, Pilet et al 2023) and systematically misperceive public preferences even among salient subgroups in the population (Sevenans et al 2021;Varone and Helfer 2021).…”
Section: Political Representation Knowledge and Gendermentioning
confidence: 99%
“…An important research question, then, is whether politicians have accurate perceptions of voter preferences. A growing body of research demonstrates that politicians hold rather inaccurate perceptions of what voters want: Politicians regularly assume that a majority of their voters supports a proposal, while most voters actually oppose it, or vice versa (see, e.g., Broockman & Skovron, 2018; Clausen et al, 1983; Eichenberger et al, 2021; Hedlund & Friesema, 1972; Norris & Lovenduski, 2004; Walgrave et al, 2022, 2023). Their perceptions being flawed, politicians risk acting unresponsively, communicating poorly, and, ultimately, disappointing citizens.…”
Section: Social Projection Among Politiciansmentioning
confidence: 99%